2021
DOI: 10.1136/bcr-2021-244014
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular osteoma as a cause of ankylosis and progressive trismus

Abstract: Osteomas are benign tumours of bone tissue restricted to the craniofacial skeleton. The aim of this article is to present and discuss the demographic and clinical aspects and the management of craniomaxillofacial osteomas. When the patient was submitted from primary care to our hospital, he was 68 years old, and he had ankylosis of the temporomandibular joint for the previos 4 years. A CT scan was performed, finding a giant mandibular osteoma. Conservative treatment and radiological follow-up were carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…O envolvimento do terço médio da face e da mandíbula pode causar assimetria facial (Tarsitano et al, 2021), quando localizado na órbita pode causar exoftalmia (Tawashi et al, 2023). O envolvimento do côndilo mandibular pode ser causa de disfunções como má oclusão, limitação de abertura bucal, e em alguns casos zumbido e surdez (Lucamba et al, 2023;Ortega Beltrá et al, 2021;Ostrofsky et al, 2019).…”
Section: Discussionunclassified
“…O envolvimento do terço médio da face e da mandíbula pode causar assimetria facial (Tarsitano et al, 2021), quando localizado na órbita pode causar exoftalmia (Tawashi et al, 2023). O envolvimento do côndilo mandibular pode ser causa de disfunções como má oclusão, limitação de abertura bucal, e em alguns casos zumbido e surdez (Lucamba et al, 2023;Ortega Beltrá et al, 2021;Ostrofsky et al, 2019).…”
Section: Discussionunclassified
“…For this reason, diagnosis may be performed when the osteoma becomes symptomatic or may be accidentally evidenced with radiological investigations with other purposes. Small osteoma may present itself with no symptoms for many years, while giant maxillofacial osteomas may disfigure the face or interfere with temporomandibular functions; Ortega Beltrá et al 4 reported a case of ankylosis of the temporomandibular joint treated with conservative treatment and radiological follow-up; Kashima reported two cases of peripheral osteoma with a significative external deformity: external deformity of the osteoma may lead to an early diagnosis, and usually no other symptoms are reported 5. Badauy et al 6 reported a similar case with a significative lingual expansion of the osteoma.…”
Section: Discussionmentioning
confidence: 99%
“…When tumors arise in the maxilla of the jaw and zygoma, 54 their growth can lead to disturbances in mastication, 55 impairment of mouth opening, 55 temporomandibular joint pain, 56 and paresthesia caused by compression of the trigeminal and mandibular nerve. In rare incidences where the osteoma arises closer to the mandibular condyle, tinnitus, and hearing loss can occur due to compression of the cochleovestibular nerve and conductive structures of the inner ear.…”
Section: Clinical Presentationmentioning
confidence: 99%